HIV Incidence Estimates Using the Limiting Antigen Avidity EIA Assay at Testing Sites in Kiev City, Ukraine: 2013-2014. - Ruth Simmons; Ruslan Malyuta; Nelli Chentsova; Iryna Karnets; Gary Murphy; Antonia Medoeva; Yuri Kruglov; Alexander Yurchenko; Andrew Copas; Kholoud Porter; CASCADE Collaboration in EuroCoord (PLoS ONE)
Objective To estimate HIV incidence and highlight the characteristics of persons at greatest risk of HIV in the Ukraine capital, Kiev. Method Residual samples from newly-diagnosed persons attending the Kiev City AIDS Centre were tested for evidence of recent HIV infection using an avidity assay. Questions on possible risk factors for HIV acquisition and testing history were introduced. All persons (≥16yrs) presenting for an HIV test April'13-March'14 were included. Rates per 100,000 population were calculated using region-specific denominators. Results During the study period 6370 individuals tested for HIV. Of the 467 individuals newly-diagnosed with HIV, 21 had insufficient samples for LAg testing. Of the remaining 446, 39 (8.7%) were classified as recent with an avidity index <1.5ODn, 10 were reclassified as long-standing as their viral load was <1000 copies/mL, resulting in 29 (6.5%) recent HIV infections. The only independent predictor for a recent infection was probable route of exposure, with MSM more likely to present with a recent infection compared with heterosexual contact [Odds Ratio 8.86; 95%CI 2.65-29.60]. We estimated HIV incidence at 21.5 per 100,000 population, corresponding to 466 new infections. Using population estimates for MSM and PWID, incidence was estimated to be between 2289.6 and 6868.7/100,000 MSM, and 350.4 for PWID. Conclusion A high proportion of persons newly-infected remain undiagnosed, with MSM disproportionally affected with one in four newly-HIV-diagnosed and one in three recently-HIV-infected. Our findings should be used for targeted public health interventions and health promotion.